Activities of wild‐type and variant tissue‐type plasminogen activators retained on vascular endothelial cells. Issue 5 (1st April 2016) - Suzuki, Yuko; Sano, Hideto; Tomczyk, Martyna; Brzoska, Tomasz; Urano, Tetsumei
Abstract : We reported that tissue‐type plasminogen activator (tPA) secreted from vascular endothelial cells (VECs) is retained on the cell surface and effectively evokes both plasminogen activation and fibrin clot dissolution (fibrinolysis) on VECs. Here, to evaluate possibly different behaviors of variants of tPA, we quantitatively assessed these two events separately using green fluorescent protein (GFP)‐conjugated tPA in cultured human VECs. The amount of secreted wild‐type tPA‐GFP correlated well with both the activities of plasminogen activation ( r = 0.66) and fibrinolysis ( r = −0.93). A variant of tPA‐GFP, with a lower affinity to the surface of VECs but higher affinity to fibrin, showed higher fibrinolysis and lower plasminogen activation activity compared to the wild‐type. Abstract : Tissue‐type plasminogen activator (tPA) secreted from vascular endothelial cells (VECs) is retained on the cell surface and evokes both plasminogen activation and fibrin clot dissolution (fibrinolysis) on VECs. Our quantitative assessment of these two different plasminogen activator activities enabled us to identify the unique characteristics of TNK‐tPA (tenecteplase), which had a lower affinity to VEC surface compared to wild‐type tPA (alteplase).